The Parallelogram Effect of Degenerative Structures Around the Apical Vertebra in Patients with Adult Degenerative Scoliosis: The Influence of Asymmetric Degeneration and Diagonal Degeneration on the Severity of Deformity - Sun, Xiang-Yao (Med Sci Monit, 2019)
BACKGROUND: This is the first published study assessing the parallelogram effect of degenerative structures around the apical vertebra. We evaluated the effect of degenerative structures around the apical vertebra and spinopelvic parameters on the severity of ADS. MATERIAL/METHODS: We retrospectively reviewed data on 144 patients with ADS. The coronal (coronal Cobb angle, CA) and sagittal (thoracic kyphosis, TK; sagittal vertical axis, SVA; pelvic incidence, PI; lumbar lordosis, LL; sacral slope, SS; pelvic tilt, PT) parameters, lumbar multifidus muscle atrophy (LMA), and facet joint osteoarthritis (FJOA) were evaluated. Multiple linear regression was used to assess the correlations. RESULTS: LL and PT were negatively correlated with CA (P<0.001), and the correlation between LL and SVA was positive (P<0.001), as was the correlation between PI and CA (P<0.001). The correlation between SS and SVA was negative (P<0.001). The correlation between CA and concave LMA at upper or lower intervertebral level of the apical vertebra was positive (P≤0.001). The convex LMA at upper and lower intervertebral levels was negatively correlated with CA (P<0.001). Convex LMA at the upper intervertebral level and concave LMA at the lower intervertebral level of the apical vertebra were negatively correlated with the SVA (P≤0.001). FJOA works similar to LMA (P<0.05). CONCLUSIONS: Spinopelvic parameters are correlated with severity of ADS. The structures around the apical vertebra are very important to maintain global alignment of the spine via the parallelogram effect.